An intellectual and human biography of Professor Luis Sánchez Granjel (Review) - Francisco Herrera Rodríguez (Universidad de Alicante, 2019)
Life and work of Luis Sánchez Granjel is the human and intellectual biography of a great master of Spanish medical historiography, carried out by José María Urkia Etxabe, Professor at the University of the Basque Country. The author has counted to make this work with the documentary background of Professor Granjel provided by the family, but also the human knowledge of his figure to have been one of his most beloved disciples.